大気から海氷表面への窒素供給過程 - 野村, 大樹; アンドリュー, マクミン; 服部, 寛; 青木, 茂; 福地, 光男; Nomura, Daiki; McMinn, Andrew; Hattori, Hiroshi; Aoki, Shigeru; Fukuchi, Mitsuo (2010)
第33回極域気水圏シンポジウム 11月30日（火） 国立極地研究所 ２階大会議室 conference object